Quarterly Earnings Announcement Effect on Stock Return and Trading Volume in Nepal (The International Research Journal of Management Science, 2019)
The study examines the stock returns and trading volume reaction to quarterly earnings announcements using the event analysis methodology. Ten commercial banks with 313 earnings announcements are considered between the fiscal year 2010/11 and 2017/18. The observations are portioned into 225 earning-increased (good-news) sub-samples and 88 earning-decreased (bad-news) sub-samples. This paper finds that the Nepalese stock market is inefficient at a semi-strong level, but there is a strong linkage between quarterly earnings announcement and trading volume. Similarly, the study provides evidence of existence of information content hypothesis in the Nepalese stock market.